(3JOGQc GdeOGQcs - (3GdOQGRj, GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s
(3ChdgG (B:s
(3jdRe ef YOe GSJaGOJg ef GdBjI GdYOe eWdbG, aEfg hEf de JOd Ydjg GdBjI(B...s
(3BNQgG (B:s
(3ef ONd Ydjg GdRhGd aj GdHdO Ke SGaQ HYO eVi GdPQGY GdPj gh hbJ GdfGadI Efg jUdj GdfGadI hjbUQ GdaQjVI MjK Efg de jONd hbJgG Ydjg aj GdMVQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B215s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B569s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B569s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs